Pembinaan IKM Maju Bersama Desa Liang Anggang dalam Meningkatkan Variasi dan Kualitas Produk Berbahan Daun Kelor: Guidance for IKM Maju Bersama with Liang Anggang Village in Increasing the Variety and Quality of Products Made from Moringa Leaves - Habibah Habibah; Rabiatul Wahdah; Norlena Safitri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Moringa is a plant that has a high nutritional content where the leaves can be used as one of the basic ingredients for food processing. The community service program was carried out in the IKM Maju Bersama group in Liang Anggang Village, Bati-Bati District, Tanah Laut Regency. The method used in this service is the counseling method by providing material related to the introduction and benefits of moringa plants, variations of moringa products and their nutritional value, as well as marketing management. In addition to providing hands-on training on making Snow White cakes, sponge cakes, puddings, meatballs and moringa nuggets. Members of the Maju Bersama IKM group have the potential to process various food products from Moringa leaves, due to the availability of Moringa plants around the group members' homes. The result of this Community Service is an increase in the knowledge and skills of the IKM Maju Bersama group regarding the use and variety of processed moringa leaf products, understanding marketing techniques and the emergence of a strong enthusiasm and desire in developing processed moringa leaf products.